Genetic structure of giant honeybee (Apis dorsata fabricius) population in Peninsular Malaysia - Sahebzadeh, Najmeh (2012)
The knowledge on the genetic structure of Apis dorsata is needed for effective management and conservation strategies of this species in Malaysia, especially to prevent over-harvesting of honey. The main objective of this research was to estimate genetic structure and relatedness of Malaysian A.dorsata populations (2009-2010) from Terengganu and Kedah using 30 DNA microsatellites. The results showed that all the loci and sample size were informative for measuring the genetic variation in A.dorsata aggregations. The results of genetic structure revealed that there was no significant deviation Hardy-Weinberg equilibrium and linkage disequilibrium (P>0.05) within and between aggregations. Population differentiation coefficient (FST) indicated a great level (FST>0.15) within five aggregations and a moderate level (FST=0.095) of genetic differentiation within an aggregation of Terengganu. A moderate level (FST>0.07) of FST was detected within Pedu Lake aggregations. The values of FST between Terengganu 2009 aggregations showed no genetic differentiation (P>0.21), whereas genetic differentiation was detected (P<0.001) between Terengganu 2010. Pair-wise of FST values between the aggregations, before (2009) and after (2010) migration, showed that two of three aggregations from Terengganu returned to their nest sites. A same result was obtained by Pedu Lake aggregations. Analysis of molecular variance (AMOVA) indicated that the nests within each aggregation were genetically and statistically distinct, as a result of the restricted drone congregation areas (DCA) of each aggregation. Amount of misclassification at assignment tests was in line with the results of FST and AMOVA, indicating two of three aggregations returned to the natal site afetr the migration (2010). The intra-colony pedigree relatedness values within aggregations showed a low level of genetic relatedness (0.29). Furthermore, genetic relatedness analyses confirmed that the queens within the aggregations were genetically different. However, presence of full and half siblings between same aggregations site before and after migration supported a probability that a particular aggregation returns to its natal site after the migration if there are available empty tree timbers. The finding of an appreciable level of aggregation fidelity indicated that a comprehensive study with a large number of aggregations throughout the region would be necessary to provide concrete proof for this idea. Finally, the genetic structure and relatedness among the solitary nests from Terengganu, 2010 showed only one nest pair were headed away by same queens. However, the finding of an appreciable level of intercolonial relatedness between the nests of A.dorsata sheds light on a larger sample size of solitary nests which were found to provide concrete proof for that particular hypothesis. This finding suggests that the formidable anthropogenic pressures may change the genetic structure of A.dorsata population in Malaysia, which still needs to be researched on in the future.